Quantitative Methods for the Study of Al—Li Alloys: Phase Composition, Anisotropy of Properties, and Phase Stability - Betsofen, S.; Grushin, I.; Knyazev, M.; Dolgova, M. (Металлофизика и новейшие технологии, 2015)
A quantitative approach to the determination of the ratio between binary and ternary intermetallic phases in the Al—Mg(Cu)—Li alloys is developed on the basis of the balance equations of the chemical and phase compositions as well as the experimentally measured lattice parameter of the α-solid solution. As shown, for the Al—Mg(Cu)—Li alloys, the ratio between the fractions of the δ′ (Al₃Li) and S₁ (T₁) phases is determined by the ratio between the molar fractions of Li and Mg (Cu). The equations for the calculation of the contents of the S₁ (Al₂MgLi), T₁ (Al₂CuLi) and δ′ (Al₃Li) phases in the 1420, 1424, 5090 alloys (Al—Mg—Li alloys) and in the 1440, 1460, 1461, 1441, 1469, 2090, 2094, 2095, 8090, Weldalite 049 alloys (Al—Cu—Li alloys) used in Russia and other countries are given. The possibilities of the method application for the study and prediction of the phase stability and anisotropy of the elastic and strength properties are considered. Розроблено кількісний підхід для визначення співвідношення бінарних і трикомпонентних інтерметалевих фаз у стопах Al—Mg(Cu)—Li, заснований на рівняннях рівноваги хемічних і фазових складів, а також експериментально виміряній сталій кристалічної ґратниці α-твердого розчину. Показано, що для стопів Al—Mg(Cu)—Li співвідношення між фракціями фаз δ′ (Al₃Li) і S₁ (T₁) визначаються співвідношенням між мольними частками Li і Mg (Cu). Наведено рівняння для розрахунку вмісту фаз S₁ (Al₂MgLi), T₁ (Al₂CuLi) і δ′ (Al₃Li) у стопах 1420, 1424, 5090 (стопи Al—Mg—Li) та у стопах 1440, 1460, 1461, 1441, 1469, 2090, 2094, 2095, 8090, Weldalite 049 (стопи Al—Cu—Li). Розглянуто можливості застосування цієї методи для вивчення та передбачення фазової стабільности й анізотропії пружніх і міцнісних властивостей. Разработан количественный подход для определения соотношения бинарных и трёхкомпонентных интерметаллических фаз в сплавах Al—Mg(Cu)—Li, основанный на уравнениях равновесия химических и фазовых составов, а также экспериментально измеренной постоянной кристаллической решётки α-твёрдого раствора. Показано, что для сплавов Al—Mg(Cu)—Li соотношение между фракциями фаз δ′ (Al₃Li) и S₁ (T₁) определяется соотношением между мольными долями Li и Mg (Cu). Приведены уравнения для расчёта содержания фаз S₁ (Al₂MgLi), T₁ (Al₂CuLi) и δ′ (Al₃Li) в сплавах 1420, 1424, 5090 (сплавы Al—Mg—Li) и в сплавах 1440, 1460, 1461, 1441, 1469, 2090, 2094, 2095, 8090, Weldalite 049 (сплавы Al—Cu—Li). Рассмотрены возможности применения данного метода для изучения и предсказания фазовой стабильности и анизотропии упругих и прочностных свойств.